Soil salinization in agriculture: Mitigation and adaptation strategies combining nature-based solutions and bioengineering - Tarolli, Paolo; Luo, Jian; Park, Edward; Barcaccia, Gianni; Masin, Roberta (iScience, 2024)
Soil salinization is among the most critical threats to agriculture and food security. Excess of salts adversely affects soil structure and fertility, plant growth, crop yield, and microorganisms. It is caused by natural processes, such as dry climates and low precipitations, high evaporation rate, poor waterlogging, and human factors, such as inappropriate irrigation practices, poor drainage systems, and excessive use of fertilizers. The growing extremization of climate with prolonged drought conditions is worsening the phenomenon. Nature-based solutions (NBS), combined with precision or conservation agriculture, represent a sustainable response, and offer benefits through revitalizing ecosystem services. This perspective explores NBS that can be adopted, along with their challenges and implementation limitations. We also argue that NBS could not be enough to combat hunger in the world’s most vulnerable regions and fully achieve the Sustainable Development Goal – Zero Hunger (SDG2). We therefore discuss their possible combination with salt-tolerant crops based on bioengineering. [Display omitted] Soil science; Agricultural science; Agricultural soil science